The tendencies of manifestation of Lithuanian national cultural identity in emigration - Strakšienė, Diana; Radzevičienė, Liuda (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2016)
Emigration is becoming a global issue throughout the world, and the cognition of characteristics of manifestations of emigration people’s national identity provides preconditions for sustainable existence of society. The article analyses experiences of people in the emigration situation, revealing the tendencies of changes in the national identity. The semi-structured interview comprised semantic blocks reflecting the manifestations of the cultural identity and self-value of Lithuanians: experiences of awareness of the individual national identity; enshrining of cultural and religious traditions in emigration. It has been found out that cultural and religious milieus as well as the enshrining national traditions are significant in supporting the cultural identity of people living in emigration.
Keywords: emigration; cultural identity; religion